Genome-Wide Association Scan Shows Genetic Variants in the FTO Gene Are Associated with Obesity-Related Traits - Scuteri, Angelo; Sanna, Serena; Chen, Wei-Min; Uda, Manuela; Albai, Giuseppe; Strait, James; Najjar, Samer; Nagaraja, Ramaiah; Orrú, Marco; Usala, Gianluca; Dei, Mariano; Lai, Sandra; et al. (PLoS genetics, 2007)
The obesity epidemic is responsible for a substantial economic burden in developed countries and is a major risk factor for type 2 diabetes and cardiovascular disease. The disease is the result not only of several environmental risk factors, but also of genetic predisposition. To take advantage of recent advances in gene-mapping technology, we executed a genome-wide association scan to identify genetic variants associated with obesity-related quantitative traits in the genetically isolated population of Sardinia. Initial analysis suggested that several SNPs in the FTO and PFKP genes were associated with increased BMI, hip circumference, and weight. Within the FTO gene, rs9930506 showed the strongest association with BMI (p = 8.6 x10(-7)), hip circumference (p = 3.4 x 10(-8)), and weight (p = 9.1 x 10(-7)). In Sardinia, homozygotes for the rare "G" allele of this SNP (minor allele frequency = 0.46) were 1.3 BMI units heavier than homozygotes for the common "A" allele. Within the PFKP gene, rs6602024 showed very strong association with BMI (p = 4.9 x 10(-6)). Homozygotes for the rare "A" allele of this SNP (minor allele frequency = 0.12) were 1.8 BMI units heavier than homozygotes for the common "G" allele. To replicate our findings, we genotyped these two SNPs in the GenNet study. In European Americans (N = 1,496) and in Hispanic Americans (N = 839), we replicated significant association between rs9930506 in the FTO gene and BMI (p-value for meta-analysis of European American and Hispanic American follow-up samples, p = 0.001), weight (p = 0.001), and hip circumference (p = 0.0005). We did not replicate association between rs6602024 and obesity-related traits in the GenNet sample, although we found that in European Americans, Hispanic Americans, and African Americans, homozygotes for the rare "A" allele were, on average, 1.0-3.0 BMI units heavier than homozygotes for the more common "G" allele. In summary, we have completed a whole genome-association scan for three obesity-related quantitative traits and report that common genetic variants in the FTO gene are associated with substantial changes in BMI, hip circumference, and body weight. These changes could have a significant impact on the risk of obesity-related morbidity in the general population.